COST OF PRODUCTION AND MARKET PRICE. - Canning, John B. (The Accounting Review, 1931)
The classification of costs into constant and variable costs has likewise played a prominent role in price theory. If any particular element of cost be written as a function of volume of production for one enterprise, the function will not hold true in others. If one write the function to express an average relation for all enterprises in an industry for a given period, the function will not be true of an earlier or of a later period. Measurements of unused capacity, in other words, are unstable quantities both with respect to different concerns, different times, and different products. The proliferation of marginal theories both with respect to marginal producers and with respect to cost of producing marginal units have been developed also. But objective criteria whereby may know who are sub-marginal, who are marginal and who are supra-marginal producers are still wanting. Neither do one know whether or not any particular producer's volume stops short of the unit that would have been marginal, or just reaches that point or goes beyond it.